Geochemical Transactions - Fein, Jeremy; Druschel, Gregory K.; Furukawa, Yoko.; Alessi, Daniel S. .; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: BioMed Central.)
Geochemical Transactions publishes high-quality research in all areas of chemistry as it relates to materials and processes occurring in terrestrial and extraterrestrial systems. The journal coverage includes, but is not limited to: organic geochemistry inorganic geochemistry marine and aquatic chemistry chemical oceanography biogeochemistry applied geochemistry astrobiology environmental geochemistry.
Keywords: Geochemistry; Environmental chemistry; Chemistry; Physical geography; Geochemistry; Environmental Chemistry; Chemistry; Earth System Sciences